Pelatihan Menulis Paragraf Narasi dengan Menggunakan EYD Edisi V dalam Rangka Optimalisasi Gerakan Literasi Sekolah di SMA Negeri 2 Dumai - Wilda Srihastuty Handayani Piliang; Syafriyani Nofitri; Erni Erni; Sri Rahayu (UIR Press, 2023)
EYD V Edition was introduced as an effort to update and improve the Indonesian spelling system. However, students' understanding of the use of EYD V Edition is still lacking, so that the effect on students' writing abilities is not optimal. Therefore, this study aims to provide special training to SMA Negeri 2 Dumai students in writing narrative paragraphs using EYD V Edition. This study uses a descriptive method involving SMA Negeri 2 Dumai students as participants. The training in writing narrative paragraphs was focused on using EYD V Edition. The results of this study showed an increase in students' ability to write narrative paragraphs after attending the training. In addition, the school principal and the monitoring team also gave a positive response to this activity. In conclusion, this study shows that training in writing narrative paragraphs using EYD V Edition can help students improve their writing skills. Mastery of good and correct spelling is an important factor in writing success, and the use of EYD V Edition can be an appropriate guide in writing Indonesian. It is hoped that this research can make a significant contribution in optimizing the literacy movement at SMA Negeri 2 Dumai and also provide input for the development of education in Indonesia broadly.